Nutritional Value of Popular Foods Offered to Monks by Thai Buddhists - Kamkokgruad, Tharika; Chatthongpisut, Rassarin; Intajarurnsan, Sutheera (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 1 (2019): January - March 2019, 2019)
Health issues have increased among monks in Thailand due to food consumption behavior diet based on food offered by Buddhists at present. Most foods offered by Thai Buddhists are often rich in carbohydrates and fat which may contribute to the monks’ declining health. The objective of this research was to survey foods and analyze nutritional value of food offered to monks by Thai Buddhists. Cross-sectional survey revealed that the most common dishes are five-spice eggs (Kai Palo), Spicy minced pork (Larb moo), sour soup with mixed vegetables (Kaeng Som Pak Reum), omelet (Kai jieow) and curry with pickled bamboo shoots (Kaeng Pet Nor Mai Dong). Simple random sampling methods were used to collect samples. Samples of these popular dishes were collected from different restaurants and recipes and analyzed using the nutritional analysis program, INMUCAL V.3. The results from each 100 g of food showed that the five-spice eggs contained the most sodium and sugar (654.70 mg and 5.53 g, respectively). Spicy minced pork provided the highest carbohydrates, protein and calories (23.98 g, 14.29 g and 231.65 kcal, respectively). The food with the highest water content and vitamin C were sour soup with mixed vegetables (88.92 and 14.04 mg, respectively). Omelet contained the highest fat and cholesterol (17.08 g and 312.06 mg, respectively). Lastly, the food with the highest fiber content was the curry with pickled bamboo shoots (1.17 g). Conclusion, the popular dishes offered to monks by Thai Buddhists are high in carbohydrates, fat, cholesterol, sugar, and sodium but provides minimal fiber. The empirical data highlighted the main causes of the hazard. It is therefore recommended that the diet be balanced by medical practitioners in order to improve the food offerings. It would be beneficial to create more awareness and educate the vendors as well as Buddhists to adjust their food offering choices and recipes. Keywords: Nutritional value, Food offering, Monks, Buddhists.